2017
DOI: 10.1007/s13384-017-0239-6
|View full text |Cite
|
Sign up to set email alerts
|

Distance travelled: outcomes and evidence in flexible learning options

Abstract: Flexible learning options (FLOs) provide individualised learning pathways for disengaged young people with strong emphasis on inclusivity and wellbeing support. Amidst a rapid expansion of Australia's flexible learning sector, service providers are under increasing pressure to substantiate participant outcomes. This paper stems from a national study of the value of FLOs to young people and the broader Australian community. The study enumerates the outcomes valued by flexible learning practitioners, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Previous studies in the field of alternative education found significance in determining qualitatively personal progress of distance travelled (Thomas et al, 2017); and the centrality of interpersonal relationships for envisaging aspirational futures (McGregor et al, 2017;Mills & McGregor, 2014;Vadeboncoeur & Vallos, 2016;Vadeboncoeur & Padilla-Petry, 2017). This paper contributes to the knowledge of community-based alternative learning environments as places free from the trappings of rigid, formal learning environments.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Previous studies in the field of alternative education found significance in determining qualitatively personal progress of distance travelled (Thomas et al, 2017); and the centrality of interpersonal relationships for envisaging aspirational futures (McGregor et al, 2017;Mills & McGregor, 2014;Vadeboncoeur & Vallos, 2016;Vadeboncoeur & Padilla-Petry, 2017). This paper contributes to the knowledge of community-based alternative learning environments as places free from the trappings of rigid, formal learning environments.…”
Section: Discussionmentioning
confidence: 73%
“…Second, at the level of the local and particular, judgements have been made about the spatial and social architectures of alternative learning environments, some of which were deemed to be innovative in their potential to engage marginalised young people (Edwards, 2018;Mills & McGregor, 2014;McGregor, Mills, te Riele et al, 2017;Thomas et al, 2017;Vadeboncoeur & Velos, 2016). Edwards's (2018) ethnographic study in the United Kingdom investigated a youth centre's alternative curriculum cocreated with disengaged secondary school students, youth leaders, family and teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Naidu's (2019) study show that learners with learning disabilities perceived flexible learning as challenging to conceptualise. It needs a personalised learning strategy for the learners, which will be difficult to administer by parents who are not experts on the learning strategy (Thomas et al, 2017). The undying issue of accessibilities and the need for resources in implementation would always be a great challenge for the teachers, learners and parents (Kadoic et al, 2017;Wong, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Music also contributes to generative learning environments when it is meaningful for children. The emotional climate of learning spaces has been shown to be vital to children's disposition to learn (Mills & McGregor, 2016;Tyng et al, 2017) and emotional wellbeing has been linked to literacy and matriculation (Thomas et al, 2017). Education providers often require children to fit into set structures and learning styles, which may be experienced as oppressive and/or combative by the school student (Mills & McGregor, 2014).…”
Section: The Learning Environment and Musicmentioning
confidence: 99%